Low-density weight-reducing heat-conducting silica gel and preparation method thereof
By surface modification of boron nitride or aluminum nitride powder and porous alumina coating, the compatibility problem between thermally conductive fillers and silicone rubber matrix was solved, achieving the preparation of thermally conductive silicone with low density, weight reduction, and high thermal conductivity.
Patent Information
- Application Number
- CN202411589519.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The compatibility and bonding force between the thermally conductive filler and the silicone rubber matrix in existing thermally conductive silicone are poor, resulting in reduced thermal conductivity and mechanical properties, which cannot meet the requirements for low density and weight reduction.
Low-density, weight-reducing, thermally conductive silicone rubber was prepared by surface modification of boron nitride or aluminum nitride powder using aluminate coupling agents and silane coupling agents, followed by porous alumina coating treatment and hot-press curing.
It significantly improves the thermal conductivity and mechanical properties of thermally conductive silicone, reduces density, and meets the requirements for lightweighting.
Smart Images

Figure BDA0005125197280000071 
Figure BDA0005125197280000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicone rubber, and in particular relates to a low-density, weight-reducing, thermally conductive silicone rubber and a preparation method thereof. Background Art
[0002] Electronic products, new energy, artificial intelligence, and smart wearables have increasingly higher requirements for product weight. Under the same performance conditions, the lower the density and the lower the weight, the smaller the loss of potential energy, and the better the user experience. For example, VR glasses, headphones, mobile phones, and smart wearable products are more sensitive to weight and have greater requirements for lightweighting.
[0003] At present, the main components of thermal conductive silicone in the industry are thermal conductive powder + flame retardant + silicone oil + hydrogen + small materials. The main component of thermal conductive powder is alumina, which has a solid spherical metal body and a normal density of 3.5-4.0g / cm 3 , high density and high specific gravity. Other raw materials used as thermal conductive fillers include boron nitride, aluminum nitride, etc. Among them, the density of conventional hexagonal boron nitride is usually 1.5-2.5g / cm 3 The density of cubic boron nitride is usually 3.0-3.5 g / cm 3 ; The conventional density of raw aluminum nitride is 2.5-3.3 g / cm 3 The thermal conductivity of boron nitride and aluminum nitride is better than that of aluminum oxide. Therefore, using boron nitride or aluminum nitride instead of aluminum oxide as a thermal conductive filler can achieve the purpose of low density and weight reduction.
[0004] In order to improve the thermal conductivity of thermally conductive silicone products, it is necessary to increase the content of thermally conductive fillers. However, the compatibility and bonding strength of thermally conductive fillers such as boron nitride and aluminum nitride with the silicone rubber matrix are poor. The increase of thermally conductive fillers will lead to a decrease in the mechanical properties of silicone rubber and fail to meet the use requirements. Generally speaking, the better the dispersion of thermally conductive fillers in the silicone rubber matrix, the better its thermal conductivity and mechanical properties. Therefore, the same thermal conductivity and mechanical properties can be achieved under the condition of a lower amount of thermally conductive fillers. The density of the silicone rubber matrix is low, and the purpose of low density and weight reduction can also be achieved by reducing the amount of thermally conductive fillers. Therefore, by improving the dispersion and bonding strength of thermally conductive fillers such as boron nitride and aluminum nitride in the silicone rubber matrix, the purpose of low density and weight reduction and the purpose of strengthening mechanical properties can be achieved.
[0005] Patent CN 110343391 A discloses a low-density, high-thermal-conductivity silicone gasket, which uses KH-151, KH-171, KH-540, KH-550, titanate and other modification agents to modify aluminum oxide, aluminum hydroxide and boron nitride to improve the dispersibility and bonding strength of thermal conductive fillers in the silicone rubber matrix. However, the direct use of the above modification agents has a poor modification effect on boron nitride and aluminum nitride, and has limited effect on improving the thermal conductivity and mechanical properties of the product. Summary of the invention
[0006] Based on the above shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing low-density weight-reducing thermally conductive silicone.
[0007] Another object of the present invention is to provide a thermally conductive silica gel prepared by the above method.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing low-density weight-reducing thermally conductive silica gel comprises the following steps:
[0010] (1) surface-modifying boron nitride and / or aluminum nitride powder with an aluminate coupling agent, and then calcining in air or oxygen to obtain porous alumina-coated boron nitride and / or aluminum nitride powder;
[0011] (2) surface-modifying the obtained porous alumina-coated boron nitride and / or aluminum nitride powder using a silane coupling agent to obtain silane coupling agent-modified boron nitride and / or aluminum nitride powder;
[0012] (3) The obtained silane coupling agent-modified boron nitride and / or aluminum nitride powder is uniformly mixed with vinyl silicone oil, hydrogen-containing silicone oil and a catalyst, and then vacuum-defoamed, and then hot-pressed and cured by a calender to obtain a low-density, weight-reducing, thermally conductive silicone.
[0013] Preferably, the particle size of the boron nitride and / or aluminum nitride powder in step (1) is 0.5 to 10 μm.
[0014] Preferably, the surface modification method in step (1) is as follows:
[0015] Boron nitride and / or aluminum nitride powder is added into a fluidized bed to make it in a suspended motion state, the temperature is raised to 60-100° C., and then an aluminate coupling agent solution is sprayed to react to obtain boron nitride and / or aluminum nitride powder with the surface modified by the aluminate coupling agent.
[0016] The invention adopts a fluidized bed and aluminate coupling agent spraying surface modification method, which has the advantages of uniform coating and good modification effect.
[0017] Preferably, the amount of the aluminate coupling agent is 5% to 20% of the mass of the boron nitride and / or aluminum nitride powder.
[0018] Preferably, the calcination temperature in step (1) is 300 to 800° C., and the calcination time is 2 to 24 hours.
[0019] The present invention pre-modifies the surface of boron nitride and / or aluminum nitride powder by using an aluminate coupling agent, and then obtains a porous aluminum oxide coating layer with strong bonding force with the boron nitride and / or aluminum nitride powder by calcination. The porous aluminum oxide coating layer has the characteristics of high specific surface area, can effectively enhance the reactivity with the silane coupling agent and the bonding force with the silicone rubber matrix, improve the dispersion effect of the thermal conductive powder in the silicone rubber matrix, thereby improving the thermal conductivity and mechanical properties. At the same time, the porous aluminum oxide coating layer has the characteristics of low density, has no obvious weight gain effect on the boron nitride and / or aluminum nitride powder, and can better maintain the low density characteristics of the boron nitride and / or aluminum nitride thermal conductive powder.
[0020] Preferably, the silane coupling agent in step (2) is at least one of an alkyl silane coupling agent, a vinyl silane coupling agent, and an epoxy silane coupling agent; more preferably, the silane coupling agent is a vinyl silane coupling agent.
[0021] The present invention further performs surface modification on the porous alumina-coated boron nitride and / or aluminum nitride powder by using a silane coupling agent, which can further improve the compatibility of the thermally conductive powder with the silicone rubber matrix and reduce the adverse effect of the thermally conductive filler on the mechanical properties of the silicone rubber. In addition, the thermally conductive filler surface-modified by the vinyl silane coupling agent can also produce a chemical cross-linking reaction with the silicone rubber matrix during the subsequent hot pressing curing molding process, further significantly improving the mechanical strength of the thermally conductive silicone rubber.
[0022] Preferably, the added amount of the silane coupling agent is 1% to 10% of the mass of the porous alumina-coated boron nitride and / or aluminum nitride powder.
[0023] Preferably, in step (3), the mass ratio of the silane coupling agent modified boron nitride and / or aluminum nitride powder to the vinyl silicone oil and hydrogen-containing silicone oil is 100:30 to 80:20 to 50.
[0024] Preferably, the catalyst in step (3) is chloroplatinic acid or Custer platinum catalyst; the amount of the catalyst is 0.005% to 0.02% of the total mass of the reaction materials.
[0025] Preferably, the mixing in step (3) means first mixing the silane coupling agent-modified boron nitride and / or aluminum nitride powder with vinyl silicone oil and hydrogen-containing silicone oil in a vacuum kneader at 100-160° C., then cooling to room temperature and adding a catalyst to mix evenly.
[0026] Preferably, the temperature of the hot pressing curing molding in step (3) is 100-150° C. and the time is 5-15 minutes.
[0027] A low-density, weight-reducing, thermally conductive silica gel is prepared by the method.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The thermally conductive filler of the present invention uses low-density boron nitride and / or aluminum nitride powder to replace aluminum oxide powder, which can achieve better thermal conductivity and weight reduction performance.
[0030] (2) The present invention uses porous alumina to coat the surface of boron nitride and / or aluminum nitride thermal conductive powder and further treats the surface with a silane coupling agent, which can significantly improve the thermal conductivity and mechanical properties of the resulting thermal conductive silicone, reduce the amount of thermal conductive filler used, and thus reduce the density of the thermal conductive silicone product. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0032] Example 1
[0033] A method for preparing low-density weight-reducing thermally conductive silica gel comprises the following steps:
[0034] (1) The particle size of D50 is 1.5 μm and the density is 2.25 g / cm 3 Add the boron nitride powder into the fluidized bed, introduce 80℃ high pressure circulating nitrogen to make it in suspension, then spray the ethyl acetate solution of aluminate coupling agent DL-411 for reaction, the amount of aluminate coupling agent is 12% of the mass of boron nitride powder, and obtain boron nitride powder with surface modified by aluminate coupling agent. Then introduce air, heat to 650℃ and calcine for 8h to obtain porous alumina coated boron nitride powder.
[0035] (2) The porous alumina-coated boron nitride powder obtained in step (1) is cooled to 60° C. by air cooling, and then sprayed with a methyltrimethoxysilane coupling agent solution for surface modification, wherein the amount of the silane coupling agent added is 5% of the mass of the porous alumina-coated boron nitride powder to obtain a silane coupling agent-modified boron nitride powder.
[0036] (3) The obtained silane coupling agent modified boron nitride powder, vinyl silicone oil and hydrogen-containing silicone oil are added into a kneader in a mass ratio of 100:50:30 and fully kneaded at 150° C., then cooled to room temperature, 0.01% Custer platinum catalyst is added and mixed evenly, vacuum defoamed, and then the material is added to a calender in a vacuum extraction manner to press out a product of corresponding thickness, and the pressed material is passed through a tunnel furnace at 140° C., 12 m, 3 min; 125° C., 10 m, 3 min; 110° C., 10 m, 2 min, thermally cured and formed, naturally cooled by air, and rolled to obtain a low-density weight-reducing thermal conductive silicone.
[0037] Example 2
[0038] A method for preparing low-density weight-reducing thermally conductive silica gel comprises the following steps:
[0039] (1) The particle size of D50 is 1.5 μm and the density is 2.25 g / cm 3 Add the boron nitride powder into the fluidized bed, introduce 80℃ high pressure circulating nitrogen to make it in a suspended motion state, then spray the ethyl acetate solution of aluminate coupling agent DL-411 for reaction, the amount of aluminate coupling agent is 5% of the mass of boron nitride powder, and obtain boron nitride powder with surface modified by aluminate coupling agent. Then introduce air, heat to 400℃ and calcine for 12h to obtain porous alumina coated boron nitride powder.
[0040] (2) The porous alumina-coated boron nitride powder obtained in step (1) is cooled to 60° C. by air cooling, and then sprayed with a methyltrimethoxysilane coupling agent solution for surface modification, wherein the amount of the silane coupling agent added is 1% of the mass of the porous alumina-coated boron nitride powder to obtain a silane coupling agent-modified boron nitride powder.
[0041] (3) The obtained silane coupling agent modified boron nitride powder, vinyl silicone oil and hydrogen-containing silicone oil are added into a kneader in a mass ratio of 100:30:20 and fully kneaded at 150° C., then cooled to room temperature, 0.01% Custer platinum catalyst is added and mixed evenly, vacuum defoamed, and then the material is added to a calender in a vacuum extraction manner to press out a product of corresponding thickness, and the pressed material is passed through a tunnel furnace at 140° C., 12 m, 3 min; 125° C., 10 m, 3 min; 110° C., 10 m, 2 min, thermally cured and formed, naturally cooled by air, and rolled to obtain a low-density weight-reducing thermally conductive silicone.
[0042] Example 3
[0043] A method for preparing low-density weight-reducing thermally conductive silica gel comprises the following steps:
[0044] (1) The particle size of D50 is 1.5 μm and the density is 2.25 g / cm 3Add the boron nitride powder into the fluidized bed, introduce 80℃ high pressure circulating nitrogen to make it in suspension, then spray the ethyl acetate solution of aluminate coupling agent DL-411 to react, the amount of aluminate coupling agent is 20% of the mass of boron nitride powder, and obtain boron nitride powder with surface modified by aluminate coupling agent. Then introduce air, heat to 750℃ and calcine for 3h to obtain porous alumina coated boron nitride powder.
[0045] (2) The porous alumina-coated boron nitride powder obtained in step (1) is cooled to 60° C. by air cooling, and then sprayed with a methyltrimethoxysilane coupling agent solution for surface modification, wherein the amount of the silane coupling agent added is 10% of the mass of the porous alumina-coated boron nitride powder to obtain a silane coupling agent-modified boron nitride powder.
[0046] (3) The obtained silane coupling agent modified boron nitride powder, vinyl silicone oil and hydrogen-containing silicone oil are added into a kneader in a mass ratio of 100:80:50 and fully kneaded at 150° C., then cooled to room temperature, 0.01% Custer platinum catalyst is added and mixed evenly, vacuum defoamed, and then the material is added to a calender in a vacuum extraction manner to press out a product of corresponding thickness, and the pressed material is passed through a tunnel furnace at 140° C., 12 m, 3 min; 125° C., 10 m, 3 min; 110° C., 10 m, 2 min, thermally cured and formed, naturally cooled by air, and rolled to obtain a low-density weight-reducing thermally conductive silicone.
[0047] Example 4
[0048] A method for preparing low-density weight-reducing thermally conductive silica gel, compared with Example 1, using an equal amount of D50 particle size of 2 μm and a density of 3.25 g / cm 3 Aluminum nitride powder replaces boron nitride powder.
[0049] Example 5
[0050] A method for preparing low-density weight-reducing thermally conductive silica gel, compared with Example 1, using an equal amount of epoxy silane coupling agent KH-560 to replace methyl trimethoxy silane coupling agent.
[0051] Example 6
[0052] A method for preparing a low-density, weight-reducing, thermally conductive silica gel, compared with Example 1, using an equal amount of vinyl trimethoxy silane coupling agent to replace the methyl trimethoxy silane coupling agent.
[0053] Comparative Example 1
[0054] A method for preparing low-density weight-reducing thermally conductive silica gel comprises the following steps:
[0055] (1) The particle size of D50 is 1.5 μm and the density is 2.25 g / cm 3The boron nitride powder is added into a fluidized bed, and then a methyltrimethoxysilane coupling agent solution is sprayed for surface modification, wherein the amount of the silane coupling agent added is 5% of the mass of the boron nitride powder, to obtain silane coupling agent-modified boron nitride powder.
[0056] (2) The obtained silane coupling agent modified boron nitride powder, vinyl silicone oil and hydrogen-containing silicone oil are added into a kneader in a mass ratio of 100:50:30 and fully kneaded at 150° C., then cooled to room temperature, 0.01% Custer platinum catalyst is added and mixed evenly, vacuum defoamed, and then the material is added to a calender in a vacuum extraction manner to extrude a product of corresponding thickness, and the pressed material is passed through a tunnel furnace at 140° C., 12 m, 3 min; 125° C., 10 m, 3 min; 110° C., 10 m, 2 min, thermally cured and formed, naturally cooled by air, and rolled to obtain a low-density weight-reducing thermal conductive silicone.
[0057] Comparative Example 2
[0058] A method for preparing low-density weight-reducing thermally conductive silica gel comprises the following steps:
[0059] (1) The particle size of D50 is 1.5 μm and the density is 2.25 g / cm 3 The boron nitride powder is added into the fluidized bed, and 80°C high-pressure circulating nitrogen is introduced to make it in a suspended motion state, and then the ethyl acetate solution of aluminate coupling agent DL-411 is sprayed to react. The amount of aluminate coupling agent is 12% of the mass of the boron nitride powder, and the boron nitride powder with the surface modified by the aluminate coupling agent is obtained.
[0060] (2) The boron nitride powder surface-modified with the aluminate coupling agent obtained in step (1) is cooled to 60° C. by air cooling, and then sprayed with a methyltrimethoxysilane coupling agent solution for surface modification, wherein the amount of the silane coupling agent added is 5% of the mass of the boron nitride powder surface-modified with the aluminate coupling agent, to obtain a silane coupling agent-modified boron nitride powder.
[0061] (3) The obtained silane coupling agent modified boron nitride powder, vinyl silicone oil and hydrogen-containing silicone oil are added into a kneader in a mass ratio of 100:50:30 and fully kneaded at 150° C., then cooled to room temperature, 0.01% Custer platinum catalyst is added and mixed evenly, vacuum defoamed, and then the material is added to a calender in a vacuum extraction manner to press out a product of corresponding thickness, and the pressed material is passed through a tunnel furnace at 140° C., 12 m, 3 min; 125° C., 10 m, 3 min; 110° C., 10 m, 2 min, thermally cured and formed, naturally cooled by air, and rolled to obtain a low-density weight-reducing thermal conductive silicone.
[0062] Comparative Example 3
[0063] This comparative example uses an equivalent D50 particle size of 1.5 μm and a density of 3.82 g / cm3 The alumina powder replaces the boron nitride powder, and the rest is the same as in Example 1.
[0064] The density (determined by the water displacement method), thermal conductivity (according to ASTM D5470-2006 standard) and tensile strength (according to GB / T 528-2009) of the thermally conductive silica gel obtained in the above examples and comparative examples were tested, and the results are shown in Table 1 below.
[0065] Table 1
[0066]
[0067]
[0068] It can be seen from the comparison results of Examples 1 to 4 and Comparative Example 3 in Table 1 that the present invention uses boron nitride or aluminum nitride powder to replace aluminum oxide powder, and the obtained thermally conductive silicone has the characteristics of low density and high thermal conductivity. It can be seen from the comparison results of Example 1 and Examples 5 to 6 that the thermally conductive silicone obtained by using vinyl silane coupling agent has higher thermal conductivity and tensile strength than other silane coupling agents. The reason is that the vinyl silane coupling agent can produce a chemical cross-linking reaction with the silicone rubber matrix during the subsequent hot pressing curing molding process, thereby improving the bonding force and compatibility between the thermally conductive filler and the silicone rubber matrix. It can be seen from the results of Comparative Example 1 that the boron nitride thermally conductive powder is not pre-coated with porous aluminum oxide, and the thermal conductivity and mechanical strength of the obtained thermally conductive silicone are significantly reduced. The reason is that the porous aluminum oxide coating layer can effectively enhance the reactivity of the thermally conductive filler with the silane coupling agent and the bonding force with the silicone rubber matrix, and improve the dispersion effect of the thermally conductive filler in the silicone rubber matrix, thereby improving the thermal conductivity and mechanical properties. It can be seen from the results of comparative example 2 that the surface modification using both aluminate coupling agent and silane coupling agent has little effect on the thermal conductivity and mechanical properties of the obtained thermally conductive silicone compared with the surface modification using only silane coupling agent, which further proves that high-temperature calcination to form a porous alumina coating is the key to improving the thermal conductivity and mechanical strength of the product.
[0069] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing low-density weight-reducing thermally conductive silica gel, characterized in that: The steps include: (1) surface-modifying boron nitride and / or aluminum nitride powder with an aluminate coupling agent, and then calcining in air or oxygen to obtain porous alumina-coated boron nitride and / or aluminum nitride powder; (2) surface-modifying the obtained porous alumina-coated boron nitride and / or aluminum nitride powder using a silane coupling agent to obtain silane coupling agent-modified boron nitride and / or aluminum nitride powder; (3) The obtained silane coupling agent-modified boron nitride and / or aluminum nitride powder is uniformly mixed with vinyl silicone oil, hydrogen-containing silicone oil and a catalyst, and then vacuum-defoamed, and then hot-pressed and cured by a calender to obtain a low-density, weight-reducing, thermally conductive silicone.
2. The method for preparing a low-density weight-reducing thermally conductive silica gel according to claim 1, characterized in that: The particle size of the boron nitride and / or aluminum nitride powder in step (1) is 0.5 to 10 μm.
3. The method for preparing a low-density weight-reducing thermally conductive silica gel according to claim 1, characterized in that: The surface modification method in step (1) is as follows: Boron nitride and / or aluminum nitride powder is added into a fluidized bed to make it in a suspended motion state, the temperature is raised to 60-100° C., and then an aluminate coupling agent solution is sprayed to react to obtain boron nitride and / or aluminum nitride powder with the surface modified by the aluminate coupling agent.
4. The method for preparing a low-density weight-reducing thermally conductive silica gel according to claim 3, characterized in that: The amount of the aluminate coupling agent used is 5% to 20% of the mass of the boron nitride and / or aluminum nitride powder.
5. The method for preparing a low-density weight-reducing thermally conductive silica gel according to claim 1, characterized in that: The calcination temperature in step (1) is 300-800° C., and the calcination time is 2-24 hours.
6. The method for preparing a low-density weight-reducing thermally conductive silica gel according to claim 1, characterized in that: The silane coupling agent in step (2) is at least one of an alkyl silane coupling agent, a vinyl silane coupling agent, and an epoxy silane coupling agent; preferably, a vinyl silane coupling agent is used.
7. The method for preparing a low-density weight-reducing thermally conductive silica gel according to claim 6, characterized in that: The added amount of the silane coupling agent is 1% to 10% of the mass of the porous alumina-coated boron nitride and / or aluminum nitride powder.
8. The method for preparing a low-density weight-reducing thermally conductive silica gel according to claim 1, characterized in that: In step (3), the mass ratio of the silane coupling agent modified boron nitride and / or aluminum nitride powder to the vinyl silicone oil and hydrogen-containing silicone oil is 100:30-80:20-50; the catalyst is chloroplatinic acid or Custer platinum catalyst; the amount of the catalyst is 0.005%-0.02% of the total mass of the reaction materials.
9. The method for preparing a low-density weight-reducing thermally conductive silica gel according to claim 1, characterized in that: The mixing in step (3) refers to first mixing the silane coupling agent modified boron nitride and / or aluminum nitride powder with vinyl silicone oil and hydrogen-containing silicone oil in a vacuum kneader at 100-160° C., then cooling to room temperature and adding a catalyst to mix evenly; the temperature of the hot pressing curing molding is 100-150° C. and the time is 5-15 minutes.
10. A low-density, weight-reducing, thermally conductive silica gel, characterized in that: It is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of high thermal conductivity alumina / epoxy resin nanocomposite material
CN109608664A
Low-density and high-thermal-conductivity silicone gasket and preparation method thereof
CN110343391A
Low-density high-thermal-conductivity silica gel as well as preparation method and application thereof
CN112778768A
Low-density high-heat-conductivity peelable single-component heat-conducting gel and preparation method thereof
CN115368739A
Coating modification method and application of aluminum nitride powder
CN115637063A